2001
DOI: 10.1590/s1516-89132001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical taxonomy of Crenicichla (Pisces: Perciformes: Cichlidae) of the Iguaçu River, Brazil

Abstract: Samples of Crenicichla iguassuensis and a morph from the Iguaçu River which differed from C. iguassuensis by its lips morphology were examined by isozyme starch electrophoresis technique. The analysis of 27 enzyme loci exhibited a genetic identity of 0.993 between the two morphs. No diagnostic locus was found that permitted to distinguish the two Crenicichla morphs. The data obtained in this investigation did not support the existence of two distinct species for this genus in the IguaçuRiver, which suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The A. altiparanae phenotypes we obtained for the 13 enzymatic systems studied were similar to those previously demonstrated for other Characiformes from the PR basin (Revaldaves et al, 1997;Renesto et al, 1997Renesto et al, , 2001Chiari and Sodré, 1999;Peres et al, 2002) and for Siluriformes (Almeida and Sodré, 1998;Zawadzki et al, 1999Zawadzki et al, , 2000aZawadzki et al, , 2000bRenesto et al, 2000). Our data revealed that A. altiparanae carries high genetic variability, 52.38% of polymorphic loci in PR and 38.10% in the RF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The A. altiparanae phenotypes we obtained for the 13 enzymatic systems studied were similar to those previously demonstrated for other Characiformes from the PR basin (Revaldaves et al, 1997;Renesto et al, 1997Renesto et al, , 2001Chiari and Sodré, 1999;Peres et al, 2002) and for Siluriformes (Almeida and Sodré, 1998;Zawadzki et al, 1999Zawadzki et al, , 2000aZawadzki et al, , 2000bRenesto et al, 2000). Our data revealed that A. altiparanae carries high genetic variability, 52.38% of polymorphic loci in PR and 38.10% in the RF.…”
Section: Discussionsupporting
confidence: 89%
“…Low estimated expected heterozygosity has also been reported for two other Iguaçu River fish, 0. 063 for Crenicichla iguassuensis (Renesto et al, 2001) and 0.024 for Pimelodus ortmanni (Renesto et al, 2000). These low expected heterozygosity values for Iguaçu River species may be due to regulation of invariable structural genes which guarantee phenotypic plasticity (Chippari-Gomes et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has evolved independently in different environments and species complexes of various New World (for example [ 50 ]) and Old World cichlids ([ 51 ] and references therein; [ 17 , 52 , 53 ]). It is considered to be a diagnostic trait: among the scores of described cichlid species (1611 Cichlidae in FishBase.org, 5 November 2009), we know of none for which the character of hypertrophied lips is a described intraspecific polymorphism (though there is debate about Crenicichla iguassuensis , see [ 54 , 55 ]).…”
Section: Discussionmentioning
confidence: 99%
“…These are different molecular forms of an enzyme catalyzing the same reaction in the cell ( Alfenas, 2006 ). Isozyme electrophoresis has been used with success to settle doubts regarding the taxonomic status of undescribed species of the Brazilian ichthyofauna ( Renesto et al , 2000 , 2001 , 2007 ; Zawadzki et al , 2000 , 2004 ).…”
Section: Introductionmentioning
confidence: 99%